Library Science Education in India: Evolution, Emerging Trends, and Challenges - Mehtab Alam Ansari; Mohammad Sharib; Naseem Eqbal (International Journal of Education Sciences, 2026)
Library and Information Science (LIS) education in India has undergone significant transformation over the past century, evolving from traditional library training to a dynamic academic discipline shaped by technological advancements and changing information needs. This study examines the origin, development, and current status of LIS education in India, with particular emphasis on its evolution in the contemporary digital environment. The research adopts a qualitative and exploratory approach and is based on secondary data collected from scholarly literature, policy documents, books, and peer-reviewed journal articles. The collected data were systematically analyzed using content analysis to understand the historical progression, emerging trends, and key challenges of LIS education in the Indian context. The study traces the historical development of LIS education from the early twentieth century to the present, highlighting the contributions of major universities and institutional initiatives that facilitated the expansion of the discipline. It also emphasizes the crucial role played by various committees and commissions, including the University Education Commission, the Kothari Commission, and the Ranganathan Committee, in shaping library education, strengthening academic libraries, and establishing professional standards for LIS education in India. The findings reveal that LIS education has transitioned from a library-centered instructional model to a technology-driven, user-oriented, and multidisciplinary field influenced by rapid developments in Information and Communication Technologies (ICT), digital libraries, data management systems, and artificial intelligence. Furthermore, the study identifies emerging trends such as curriculum modernization, digital integration, interdisciplinary learning, and skill-based training designed to meet the evolving demands of the information society. Despite these developments, the study highlights several persistent challenges, including outdated curricula in certain institutions, infrastructural constraints, inadequate funding, shortage of qualified faculty, and concerns related to the employability of LIS graduates. The study concludes that continuous curriculum reform, stronger technological integration, and enhanced institutional support are essential to ensure the long-term relevance and sustainability of LIS education in India.
Keywords: India; LIS education; education; national education policy; national knowledge commission